A review on bioenergy production from duckweed. (June 2022) - Chen, Guanyi; Zhao, Kaige; Li, Wanqing; Yan, Beibei; Yu, Yingying; Li, Jian; Zhang, Yingxiu; Xia, Shaige; Cheng, Zhanjun; Lin, Fawei; Li, Liping; Zhao, Hai; et al.
Abstract: Duckweed easily growing in wastewater and absorbing a large amount of nitrogen and phosphorus from wastewater is now being considered as a promising solution to treat eutrophic water. However, if it is not salvaged in time, its rapid accumulation will cause secondary pollution to the water body. Duckweed is rich in protein and starch, but the content of lignin is rather low, making it an ideal biomass feedstock for energy production. This work reviews the detailed steps for producing bio-oil, bio-ethanol, biogas and other kinds of bioenergy from duckweed through hydrothermal liquefaction, pyrolysis, anaerobic digestion and fermentation processes. The reaction pathways of duckweed to produce bio-oil and bioethanol are introduced in detail. Opportunities and challenges of each conversion technology are thereafter discussed. The viability of producing biofuels and industrial precursors in a sustainable mode is also assessed. According to the characteristics of different kinds of duckweed, appropriate utilization methods should be applied to produce bioenergy to realize environmental, economic and energy benefits. Graphical abstract: Image 1 Highlights: Rapid growth and biochemical composition make duckweed a promising energy resource. Bioenergy production from duckweed coping with energy shortage and water eutrophication simultaneously. Biochemical composition of duckweed is a decisive factor of subsequent utilization and derived products. The prospects of duckweed in high value-added industrial precursors production are encouraging.